Evaluation of cushuro (Nostoc sphaericum) as an alternative source of minerals, functional protein and bioactive peptides - Chasquibol Silva, Nancy Ascención (2025)
Cushuro (Nostoc sphaericum) is an underexplored blue-green alga currently used as a food ingredient, natural medicine, and organic fertilizer in Peru. Our paper aims to address the nutritional and biological values of cushuro protein. Dried cushuro had a high amount of minerals as calcium (567 ± 64 mg/100 g to 1357 ± 153 mg/100 g), iron (13.5 ± 1.5 mg/100 g to 26.2 ± 2.9 mg/100 g, magnesium (95 ± 11 mg/100 g to 126 ± 14 mg/100 g) and protein content (32.4 ± 0.5 g/100 g to 36.9 ± 0.2 g/100 g. Protein solubility was assessed to optimize the extraction of cushuro protein by ultrasound-microwave assisted extraction, after that, the protein contents in cushuro fractions were over 70%. All detected cushuro protein fractions had Mw < 24 kDa and a better digestibility than legume products. In addition, cushuro protein products tend to have umami taste, and does not bring a bitter flavor. Moreover, cushuro flour and protein fractions contain all essential amino acids, which are responsible for over 40% of total amino acids. Meanwhile, hydrophobic amino acids content of around 40 g/100 g also indicated their excellent antioxidant potential. Thus, the data obtained supports cushuro as a promising alternative source for minerals, protein and bioactive peptides.